Kenya : Debt Sustainability Analysis. (IMF Staff Country Reports; Country Report ;, 2004)
This report of the Debt Sustainability Analysis (DSA) indicates that the envisaged strategy of a partial substitution of domestic debt by increased inflows of external grants and concessional loans, as well as a rescheduling of external debt by the Paris and London Clubs, would facilitate the achievement of debt sustainability. The DSA also confirms that such a debt rescheduling could constitute an appropriate exit strategy for Kenya. The DSA also shows that debt sustainability would improve significantly with a concessional rescheduling, particularly under the Naples terms.